Pictures Library of Smoking Cravings: Development and Verification of Smokers and Non-smokers - Gu, Zhongke; Zheng, Hui; Yin, Zhifei; Cai, Huiting; Li, Yongqiang; Zhao, Chunchun; Zhai, Yujia; Xu, Kai; Xue, Lian; Xu, Xingjun; Shen, Ying; Yuan, Ti-Fei (Frontiers in Psychiatry, 2021)
Background: The cue-induced craving by addiction related materials is commonly employed in addiction research; however, no existing standardized picture database based on the expectation model of craving has been developed. We prepared and validated a Pictures Library of Smoking Cravings (PLSC) in this study. Methods: We captured pictures 366 smoking and 406 control pictures (matched in content). We selected 109 smoking pictures and 115 control pictures and asked participants to provide ratings of craving, familiarity, valence, and arousal induced in them. Participants were divided into three groups: non-smokers (n = 211), light smokers (n = 504), and heavy smokers (n = 101). Results: The results showed that smoking pictures evoked a greater craving, familiarity, and arousal than control pictures in smokers (ps < 0.01). In addition, craving caused by smoking pictures was positively associated with the Fagerström test for nicotine dependence score in dependent smokers. Conclusions: Overall, the contemporary results showed that PLSC is effective and can be used in smoking-related studies.